Numerical simulation of the casting process of an AZ91D magnesium alloy under a rotating-pulsed combined electromagnetic field - Liang, Zhong; Bai, Qingwei; Tian, Yingchun; Liu, Yang; Zhang, Kaihua; Lai, Haomin (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
Taking an AZ91D magnesium alloy as the research object, a three-dimensional (3D) numerical model was established and simulated by simulation analysis software. The effects of a rotating electromagnetic field (REMF), a pulsed electromagnetic field (PEMF) and a rotating pulsed electromagnetic field (R-PEMF) on the magnetic field and flow field of a metal melt were studied. The simulation results show that a rotational force is generated on the cross section of the melt during the REMF treatment, and the PEMF causes magnetic pressure on the cross section of the melt. Under the combined action of the two, the Lorentz force parallel to the melt axis increases, and a secondary flow pointing to the core of the melt is generated, which helps to homogenize the melt. By analyzing the solidification structure and elemental distribution of the metal, it was shown that R-PEMF effectively improved the solidification structure and macrosegregation of the Al in the AZ91D magnesium alloy.